Systematic review and meta-analysis: A glossary - Wong, Li Ping (Faculty of Medicine, University of Malaya, 2007)
Systematic review is a comprehensive review of research findings in which all of the primary studies are systematically identified, appraised and summarised using an explicit and reproducible methodology. Meta-analysis is the statistical component of a systematic review in which combinable studies are drawn together via a statistical process. Systematic reviews and meta-analyses are routinely being used in the evidence-based approach to medicine. These short notes intend to highlight important terms in systematic-review and meta-analysis. It is a beginner's guide for health care professional of any discipline involved in research or practice who seeks to gain more comprehensive understanding of important terms used in systematic review and meta-analysis.